2013
DOI: 10.1007/s40333-013-0196-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of grazing and mowing on reproductive behaviors of Stipa grandis and Stipa krylovii in a semi-arid area

Abstract: Disturbance can affect biomass allocation of plants, but can it influence plant reproductive behavior? To address this issue, we performed field plant community investigations and explored the reproductive behaviors of Stipa grandis and Stipa krylovii in response to grazing and mowing treatments at Maodeng pasture of Xilinguole League of Inner Mongolia, China during 2007-2009. The results showed that, with a similar niche width for the two plant species under mowing and grazing treatments, mowing significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Thirdly, though the effects of the two disturbances were different, the tradeoffs for plant allocation to stems or leaves were similar. Thus, these results implied that the traits and tradeoffs were similar under the different forms of defoliation and plants responded to the stress of defoliation in a similar way [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, though the effects of the two disturbances were different, the tradeoffs for plant allocation to stems or leaves were similar. Thus, these results implied that the traits and tradeoffs were similar under the different forms of defoliation and plants responded to the stress of defoliation in a similar way [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…To adapt to stress, under certain resources, an increase in input to one organ will inevitably lead to a decrease in input to another organ. By balancing and adjusting resource allocation, especially between growth and reproduction, life history traits are optimized (Gao, Gao, & XingDong, ; Begay, Alexander, & Questad, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hickman and Hartnett found that grazing decreased the reproductive biomass allocation in Amorpha canescens Pursh, a tall perennial grass (Hickman & Hartnett, 2002). In contrast, Gao, Gao & He (2014) reported that grazing increased the reproductive biomass allocation in Stipa grandis P.A. Smirn, a perennial tussock grass.…”
Section: Discussionmentioning
confidence: 99%